Answer:
y= −1 + x/3
Step-by-step explanation:
Isolate the variable by dividing each side by factors that don't contain the variable.
Answer:
y=1/4x+3
Step-by-step explanation:
To find the inverse, switch x and y or f(x)
f(x)=4x-12
y=4x-12
x=4y-12
Add 12 to both sides
x+12=4y-12+12
x+12=4y
Divide both sides by 4
x+12/4=y
1/4x+12/4=y
1/4x+3=y
y=1/4x+3
Answer: D) cube root of 16
================================================
Explanation:
The rule we use is
![x^{m/n} = \sqrt[n]{x^m}](https://tex.z-dn.net/?f=x%5E%7Bm%2Fn%7D%20%3D%20%5Csqrt%5Bn%5D%7Bx%5Em%7D)
In this case, x = 4, m = 2 and n = 3.
So,
![x^{m/n} = \sqrt[n]{x^m}\\\\\\4^{2/3} = \sqrt[3]{4^2}\\\\\\4^{2/3} = \sqrt[3]{16}\\\\\\](https://tex.z-dn.net/?f=x%5E%7Bm%2Fn%7D%20%3D%20%5Csqrt%5Bn%5D%7Bx%5Em%7D%5C%5C%5C%5C%5C%5C4%5E%7B2%2F3%7D%20%3D%20%5Csqrt%5B3%5D%7B4%5E2%7D%5C%5C%5C%5C%5C%5C4%5E%7B2%2F3%7D%20%3D%20%5Csqrt%5B3%5D%7B16%7D%5C%5C%5C%5C%5C%5C)
Showing that the original expression turns into the cube root of 16.
Answer:
Im sorry for you this is too complex